2019
DOI: 10.1002/ana.25394
|View full text |Cite
|
Sign up to set email alerts
|

Genotype, extrapyramidal features, and severity of variant ataxia‐telangiectasia

Abstract: Objective Variant ataxia‐telangiectasia is caused by mutations that allow some retained ataxia telangiectasia‐mutated (ATM) kinase activity. Here, we describe the clinical features of the largest established cohort of individuals with variant ataxia‐telangiectasia and explore genotype‐phenotype correlations. Methods Cross‐sectional data were collected retrospectively. Patients were classified as variant ataxia‐telangiectasia based on retained ATM kinase activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 32 publications
5
69
0
4
Order By: Relevance
“…In particular, neurological evaluations were comprised of the Scale for the Assessment and Rating of Ataxia (SARA) (27), the Inventory of Non-Ataxia Signs (INAS) (29), Activities of Daily Living (ADL) (35), the SCA Functional Index (SCAFI) (36), the Composite Cerebellar Functional Severity Score (CCFS) (37), and a gait mobility score. Of note, the gait mobility score was determined by R.H., based on the Schon et al scale (66) to provide a classification for the current level of mobility for each participant. This scale is comprised of five levels of motor functionality: 0-asymptomatic, 1impaired gait (no assistance required), 2-impaired gait (utilizes cane when ambulating), 3requires walker, 4-wheelchair bound, 5-bedridden.…”
Section: Clinical Assessment Of Sca3 Participantsmentioning
confidence: 99%
“…In particular, neurological evaluations were comprised of the Scale for the Assessment and Rating of Ataxia (SARA) (27), the Inventory of Non-Ataxia Signs (INAS) (29), Activities of Daily Living (ADL) (35), the SCA Functional Index (SCAFI) (36), the Composite Cerebellar Functional Severity Score (CCFS) (37), and a gait mobility score. Of note, the gait mobility score was determined by R.H., based on the Schon et al scale (66) to provide a classification for the current level of mobility for each participant. This scale is comprised of five levels of motor functionality: 0-asymptomatic, 1impaired gait (no assistance required), 2-impaired gait (utilizes cane when ambulating), 3requires walker, 4-wheelchair bound, 5-bedridden.…”
Section: Clinical Assessment Of Sca3 Participantsmentioning
confidence: 99%
“…A milder type of A-T designated "variant A-T" is caused by biallelic variants with at least one missense or splice site mutation resulting in expression of ATM with some residual kinase activity (Dörk, Bendix-Waltes, Wegner, & Stumm, 2004;Schon et al, 2019;Sutton et al, 2004;Taylor, Lam, Last, & Byrd, 2015;Verhagen et al, 2012). Previous reports described a wide range of ATM missense and leaky splice site mutations, associated with relatively mild phenotypes (Schon et al, 2019). Due to the atypical presentation, these phenotypes often go undiagnosed for years, and many subjects with variant A-T receive the correct diagnosis only in adulthood (van Os et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been suggested that mainly the mutation type predicts the clinical course with missense variants leading to a milder phenotype but an increased risk of cancer. 5…”
Section: Discussionmentioning
confidence: 99%
“…4 The broad phenotypic spectrum of A-T now becomes gradually disentangled owing to the increased availability of comprehensive genetic testing. 5…”
mentioning
confidence: 99%